PARTNER READING STRATEGY : An Effective Strategy for Improving Students’ Reading Comprehension - Hajjah Zulianti; Tommy Hastomo (Universitas Muhammadiyah Metro, 2022)
The researchers decided to implement Partner Reading Strategy in this research because it is an effective strategy for improving the students’ reading comprehension.The students worked together to read, analyze, and discuss the text assigned in this cooperative learning strategy. This research aimed to help the students of the VIII C class of MTs N 1 Lampung Tengah improve their reading comprehension using the Partner Reading Strategy and identify their engagement in learning activities. This research used a Classroom Action Research method as research design. Partner Reading Strategy is independent variable and students’ reading comprehension is dependent variable. The subject of this research were 31 students, consisted eleven (11) male students and twenty (20) female students. The researchers used some instruments to assess students' reading comprehension that consist of formative test and summative test. In collecting the data, the writers used non-tests, including interviews, observation sheets, questionnaires, and field notes. The improvement of students' reading comprehension can be concluded from the improvement of the mean score of pre-test, formative test, and summative test. The summative test was given in the last meeting of each cycle. The result shows that using the Partner Reading Strategy successfully improved students’ reading comprehension. Moreover, students’ engagement played an influential role and impacted their learning outcomes. Implementing a Partner Reading Strategy can make students be involved in the educational activity and have a high level of engagement so that they can earn high learning outcomes.